2002
DOI: 10.1039/b202651c
|View full text |Cite
|
Sign up to set email alerts
|

Selective attachment of pyrenyl groups to ethylene-co-vinyl acetate copolymers: dynamic and static fluorescence studies

Abstract: Micromorphology is an important factor in determining polymer properties and uses. Here, steady-state and dynamic fluorescence from covalently attached 1-alkylpyrenyl groups are used to investigate the micromorphology of several random ethylene-co-vinyl acetate (EVA) copolymers with defined compositions of vinyl acetate monomer. The results are compared with those from homopolymers of high- and low-density polyethylenes and poly(vinyl acetate). Selective attachment of pyren-1-yl groups to polymer chains was ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
12

Year Published

2003
2003
2011
2011

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 35 publications
1
18
0
12
Order By: Relevance
“…The tacticity of the PMAA was determined by 13 (-C(α)-)), together with the 1 H NMR signal of the CH 3 (broad band at 0.98 ppm which shifts to low field and splits into two peaks with temperature), are in agreement with the spectroscopic behavior of the reported data for atactic PMAA. 38,39 …”
Section: Polymer Propertiessupporting
confidence: 85%
See 1 more Smart Citation
“…The tacticity of the PMAA was determined by 13 (-C(α)-)), together with the 1 H NMR signal of the CH 3 (broad band at 0.98 ppm which shifts to low field and splits into two peaks with temperature), are in agreement with the spectroscopic behavior of the reported data for atactic PMAA. 38,39 …”
Section: Polymer Propertiessupporting
confidence: 85%
“…11,12 The polymer local dynamics as well as the structural properties and relaxation processes of polymer and blends were studied by steady state and dynamic fluorescence using anthranyl and pyrenyl groups. [13][14][15] Fluorescence studies of polymethacrylic acid (PMAA) and polyacrylic acid (PAA) containing aromatic fluorescent probes such as naphthalene, anthracene and pyrene have been carried out by many authors to elucidate the properties of those polyelectrolytes in different solvents, pH, and surfactant addition. [16][17][18][19][20] Fluorescence anisotropy reflects the microviscosity and the solubilization dynamics of the probe molecule in solutions of polyelectrolytes.…”
Section: Introductionmentioning
confidence: 99%
“…1,2,[5][6][7][8][9][10][11][12][13] There are two general methodologies to incorporate dyes into polymeric materials: one produces a solid-state solution where the dye is a guest in a polymer host. 15,16 Usually, for technological purposes this is a less employed methodology since very low concentrations of the dye can be incorporated into the material. 1 The second methodology uses chemical attachment of the dye in the polymer chain either by chemical modification of the pre- formed polymer or by polymerization reactions using a monomer labeled with the azo-dye.…”
Section: Introductionmentioning
confidence: 99%
“…1 The second methodology uses chemical attachment of the dye in the polymer chain either by chemical modification of the pre- formed polymer or by polymerization reactions using a monomer labeled with the azo-dye. 1,9,10,[13][14][15][16] For both types of materials films can be prepared by casting, spin coating, self-assembly or Langmuir-Blodgett monolayer deposition. 1,9,10,12,13 Moreover, the alignment of the azodyes in polymer matrices should be induced by several types of methodologies including poling, 17 deposition by self-assembling 1,6 or by Langmuir-Blodgett, 1,6,13 by macroscopic stretching 18,19 or by photoinduction.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, we have found that pyrene, *Foreign Member of Academia Brasileira de Ciências Correspondence to: Richard G. Weiss E-mail: weissr@georgetown.edu when doped in films and irradiated with > 300 nm radiation (Naciri and Weiss 1989, Luo et al 2002, Brown et al 2002c, Yamaki et al 2002, can be covalently attached to chains of polyethylene and other polymers. In an effort to determine the sites within the polymer matrices most likely to lead to attachment, the consequences of irradiations of pyrene in a series of n-alkanes and an alkene were examined while monitoring the influences of radiation wavelength, solvent phase, pyrene concentration, and alkane chain length on the efficiency and selectivity of attachment (Zimerman and Weiss 1999).…”
Section: Introductionmentioning
confidence: 99%